9/4-2/5
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\dfrac{5}{7}\times\dfrac{5}{9}+\dfrac{4}{9}\times\dfrac{5}{7}\)
\(=\dfrac{5}{7}\times\left(\dfrac{4}{9}+\dfrac{5}{9}\right)\)
\(=\dfrac{5}{7}\times1\)
\(=\dfrac{5}{7}\)
b) \(\dfrac{1}{10}+\dfrac{5}{9}+\dfrac{4}{9}+\dfrac{9}{10}-1\)
\(=\left(\dfrac{5}{9}+\dfrac{4}{9}\right)+\left(\dfrac{1}{10}+\dfrac{9}{10}-1\right)\)
\(=1+0\)
\(=1\)
c) \(\dfrac{5}{7}\times\dfrac{5}{9}+\dfrac{4}{9}\times\dfrac{5}{7}+\dfrac{2}{7}\)
\(=\dfrac{5}{7}\times\left(\dfrac{5}{9}+\dfrac{4}{9}\right)+\dfrac{2}{7}\)
\(=\dfrac{5}{7}+\dfrac{2}{7}\)
\(=1\)
d) \(\dfrac{2}{7}+\dfrac{2}{8}+\dfrac{1}{4}+\dfrac{1}{7}+\dfrac{4}{7}\)
\(=\left(\dfrac{2}{8}+\dfrac{1}{4}\right)+\left(\dfrac{2}{7}+\dfrac{1}{7}+\dfrac{4}{7}\right)\)
\(=\left(\dfrac{1}{4}+\dfrac{1}{4}\right)+1\)
\(=\dfrac{1}{2}+1\)
\(=\dfrac{3}{2}\)
e) \(\dfrac{4}{5}+\dfrac{3}{10}+\dfrac{2}{10}+0,7\)
\(=\dfrac{4}{5}+\dfrac{5}{10}+\dfrac{7}{10}\)
\(=\dfrac{4}{5}+\dfrac{12}{10}\)
\(=\dfrac{4}{5}+\dfrac{6}{5}\)
\(=\dfrac{10}{5}\)
\(=2\)
g) \(362\times728+326\times272\)
\(=326\times\left(728+272\right)\)
\(=326\times1000\)
\(=326000\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1: =1/8*9/4=9/32
2: =8/27*243/32=9/4
3: =(5/4*4/5)^5*(4/5)^2=16/25
4: \(=\left(-\dfrac{5}{6}\cdot\dfrac{6}{5}\right)^2\cdot\left(\dfrac{6}{5}\right)^2=\dfrac{36}{25}\)
5: \(=\left(-\dfrac{4}{3}\right)^3\cdot\left(\dfrac{3}{4}\right)^{10}=\left(-1\right)\left(\dfrac{3}{4}\right)^7=-\left(\dfrac{3}{4}\right)^7\)
6: \(=\left(\dfrac{1}{3}\cdot\dfrac{-9}{2}\right)^4\left(-\dfrac{9}{2}\right)^2=\left(-\dfrac{3}{2}\right)^4\cdot\dfrac{81}{4}=\dfrac{9}{4}\cdot\dfrac{81}{4}=\dfrac{729}{16}\)
8: =(0,2*5)^4*5^2=25
10: =-0,5^5*2^10
=-0,5^5*2^5*2^5
=-32
13: =(0,5*2)^2*2^2=4
![](https://rs.olm.vn/images/avt/0.png?1311)
3 × 4 = 12 | 2 × 6 = 12 | 4 × 3 = 12 | 5 × 6 = 30 |
3 × 7 = 21 | 2 × 8 = 16 | 4 × 7 = 28 | 5 × 4 = 20 |
3 × 5 = 15 | 2 × 4 = 8 | 4 × 9 = 36 | 5 × 7 = 35 |
3 × 8 = 24 | 2 × 9 = 18 | 4 × 4 = 16 | 5 × 9 = 45 |
![](https://rs.olm.vn/images/avt/0.png?1311)
Lời giải chi tiết:
2 = 1 + 1 |
6 = 2 + 4 |
8 = 5 + 3 |
10 = 8 + 2 |
3 = 1 + 2 |
6 = 3 + 3 |
8 = 4 + 4 |
10 = 7 + 3 |
4 = 3 + 1 |
7 = 6 + 1 |
9 = 8 + 1 |
10 = 6 + 4 |
4 = 2 + 2 |
7 = 5 + 2 |
9 = 7 + 2 |
10 = 5 + 5 |
5 = 4 + 1 |
7 = 4 + 3 |
9 = 6 + 3 |
10 = 10 + 0 |
5 = 3 + 2 |
8 = 7 + 1 |
9 = 5+ 4 |
10 = 0 + 10 |
6 = 5 + 1 |
8 = 6 + 2 |
10 = 9 + 1 |
1 = 0 + 1 |
2=1+1 6=2+4 8=5+3 10=8+2
3=1+2 6=3+3 8=4+4 10=7+3
4=3+1 7=6+1 9=8+1 10=6+4
4=2+2 7=5+2 9=7=2 10=5+5
5=4+1 7=4+3 9=6+3 10=10+0
5=3+2 8=7+1 9=5=4 10=0+10
6=5+1 8=6=2 10=9+1 1=0+1
![](https://rs.olm.vn/images/avt/0.png?1311)
8 + 1 = 9 7 + 2 = 9 6 + 3 = 9 5 + 4 = 9
1 + 8 = 9 2 + 7 = 9 3 + 6 = 9 4 + 5= 9
9 - 8 = 1 9 - 7 = 2 9 - 6 = 3 9 - 5 = 4
9 - 1 = 8 9 - 2 = 7 9 - 3 = 6 9 - 4 = 5
![](https://rs.olm.vn/images/avt/0.png?1311)
a) Ta có: \(\dfrac{-5}{7}\left(\dfrac{14}{5}-\dfrac{7}{10}\right):\left|-\dfrac{2}{3}\right|-\dfrac{3}{4}\left(\dfrac{8}{9}+\dfrac{16}{3}\right)+\dfrac{10}{3}\left(\dfrac{1}{3}+\dfrac{1}{5}\right)\)
\(=\dfrac{-5}{7}\cdot\dfrac{3}{2}\cdot\dfrac{21}{10}-\dfrac{3}{4}\cdot\dfrac{56}{3}+\dfrac{10}{3}\cdot\dfrac{8}{15}\)
\(=\dfrac{-9}{4}-14+\dfrac{16}{9}\)
\(=\dfrac{-1621}{126}\)
b) Ta có: \(\dfrac{17}{-26}\cdot\left(\dfrac{1}{6}-\dfrac{5}{3}\right):\dfrac{17}{13}-\dfrac{20}{3}\left(\dfrac{2}{5}-\dfrac{1}{4}\right)+\dfrac{2}{3}\left(\dfrac{6}{5}-\dfrac{9}{2}\right)\)
\(=\dfrac{-17}{26}\cdot\dfrac{13}{17}\cdot\dfrac{-3}{2}-\dfrac{20}{3}\cdot\dfrac{3}{20}+\dfrac{2}{3}\cdot\dfrac{-33}{10}\)
\(=\dfrac{3}{4}-1-\dfrac{11}{5}\)
\(=-\dfrac{49}{20}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(9+2+5+3+7+8+4+2+9+6+4+65+6+7+4+6+3+7+4+8+5+9+08+87+1+2+3+4+2+3+2+5+6+767+5+75+6+4+6+5+66+5+7+546+46+43+6+3+6+4+6+7+8878+68+68+6+7+9+9=10961\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1) Ta có: \(\frac{-4}{7}-\frac{11}{19}+\frac{13}{19}\cdot\frac{-3}{7}+\frac{2}{19}:\frac{-7}{4}\)
\(=\frac{-4}{7}-\frac{11}{19}-\frac{39}{133}-\frac{8}{133}\)
\(=\frac{-76}{133}-\frac{77}{133}-\frac{39}{133}-\frac{8}{133}\)
\(=\frac{-200}{133}\)
2) Ta có: \(\left(\frac{-4}{9}+\frac{3}{5}\right):\frac{1}{\frac{1}{5}}+\left(\frac{1}{5}-\frac{5}{9}\right):\frac{1}{\frac{1}{5}}\)
\(=\left(\frac{-4}{9}+\frac{3}{5}\right)\cdot\frac{1}{5}+\left(\frac{1}{5}-\frac{5}{9}\right)\cdot\frac{1}{5}\)
\(=\frac{1}{5}\left(\frac{-4}{9}+\frac{3}{5}+\frac{1}{5}-\frac{5}{9}\right)\)
\(=\frac{1}{5}\left(-1+\frac{4}{5}\right)\)
\(=\frac{1}{5}\cdot\frac{-1}{5}=\frac{-1}{25}\)
3) Ta có: \(\frac{4}{5}-\left(-\frac{2}{7}\right)-\frac{7}{10}\)
\(=\frac{4}{5}+\frac{2}{7}-\frac{7}{10}\)
\(=\frac{56}{70}+\frac{20}{70}-\frac{49}{70}\)
\(=\frac{27}{70}\)
4) Ta có: \(\frac{2}{7}-\left(-\frac{13}{15}+\frac{4}{9}\right)-\left(\frac{5}{9}-\frac{2}{15}\right)\)
\(=\frac{2}{7}+\frac{13}{15}-\frac{4}{9}-\frac{5}{9}+\frac{2}{15}\)
\(=\frac{2}{7}+1-1=\frac{2}{7}\)
\(\dfrac{9}{4}-\dfrac{2}{5}=\dfrac{45}{20}-\dfrac{8}{20}=\dfrac{37}{20}\)
= 45/20 - 8/20 = 37/20